Role of the general practitioner in providing early intervention for youth mental health: a mixed methods investigation. Issue 2 (22nd December 2015) - Leahy, Dorothy; Schaffalitzky, Elisabeth; Saunders, Jean; Armstrong, Claire; Meagher, David; Ryan, Patrick; Dooley, Barbara; McNicholas, Fiona; McGorry, Patrick; Cullen, Walter
Abstract: Introduction: Youth suicide in Ireland is now the second highest in the European Union. General practitioners (GPs), as the health‐care professional most often consulted by young people, have a central role in early detection of youth mental health problems. However, evidence regarding the perspectives of young people and health‐care workers towards screening and treatment for such issues in primary care in Ireland is lacking. Aim: This study aimed to examine the role of GP in providing early intervention and treatment for youth mental health problems. Methods: A mixed methods study that involved qualitative interviews with health‐care workers from primary care, secondary care and community agencies ( n = 37) and young people ( n = 20) in two of Ireland's most socioeconomically disadvantaged areas and a national cross‐sectional survey of GPs ( n = 175) were carried out. Results: GP satisfaction rates were low in regard to postgraduate training received in child and adolescent mental health (17%) and substance use (21%). Key barriers to treatment included the attitude of patients/families, lack of specialist staff, poor service availability and time. Access to services (66%), knowing which interventions can be initiated in primary care (44%), having appropriate time and space (47%) and access to a youth worker (42%) were the interventions most commonly identified that would facilitate screening and treatment. Conclusion: The research outlined potential implications for clinical practice, research and education such as promoting awareness of mental health and the role of the GP in helping these issues, education of practitioners and improving access to psychological treatments.